Impact of COVID-19 pandemic on tuberculosis - Sae Pol; Pooja Shah; Vaishali Gaikwad; Sujata Dharmshale; Mansi Rajmane; Rajesh Karyakarte (Medical Laboratory Journal, 2025)
Background: Tuberculosis (TB) is a disease of the respiratory system that spreads when a patient coughs, sneezes, or spits. COVID-19, another respiratory disease, created havoc in 2020 and 2021.  During this pandemic, the whole healthcare system was diverted into COVID-19 patient care. It is important to determine what the status of TB was during the COVID-19 period. This study was mainly undertaken to detect the occurrence of Mycobacterium tuberculosis (M. tuberculosis) and rifampicin resistance before, during, and after COVID-19 restrictions were fully released. Methods: Pulmonary and extrapulmonary samples from 1st January 2018 till 31st December 2022 were included in the present retrospective study. The period was divided as- 2018, 2019 - Before COVID-19 2020, 2021 -COVID-19 period with restrictions (Such as use of masks, social distancing, avoiding gatherings) 2022 -COVID-19 period without restrictions. All samples received in TB section were subjected to Cartridge-Based Nucleic Acid Amplification Test (CBNAAT). The samples were processed according to the manufacturer’s guidelines. Results: There was no significant difference in samples received per year from 2018 to 2022. The positivity of M. tuberculosis decreased from 22.52% in the pre-COVID-19 period to 15.70% in the COVID-19 period with restrictions and increased again in 2022 (16.80%). Rifampicin resistance decreased from 10.40% to 6.89% in the COVID-19 period with restrictions. A decrease in positivity was not observed in extrapulmonary TB cases. Conclusion: In the present study, total samples for TB received over five years were relatively the same. Restrictions imposed during the COVID-19 period could decrease TB and rifampicin resistance. Thus, imposing restrictions on TB-suspected and positive patients regularly can help prevent the spread of the disease.